SPATIAL DISTRIBUTION OF CLAY MINERALS IN GUANABARA BAY SEDIMENTS AND ITS RELATIONSHIP WITH THE ESTUARY HYDRODYNAMICS - Patchineelam, Soraya Maia; Neto, José Antônio Baptista (Geochimica Brasiliensis, 2012)